Temperature dependent dynamics in highly homologous adenylate kinases. Issue 8 (24th May 2019) - Mohamadnezhadi, Himan; Beiramzadeh, Alireza; Shadman Lakmehsari, Muhammad; Khalifeh, Khosrow; Heshmati, Emran
Abstract: To correlate the structural features of enzymes to temperature adaptation, we studied psychrophile, mesophile, and thermophile adenylate kinases as model enzymes using bioinformatics and computational tools. Phylogenetic analysis revealed that mesophile and thermophile variants are clustered in one stem of phylogenetic tree and are close to contemporary time, while psychrophile enzyme is more close to their common ancestor. This finding is in good agreement with the process of environmental changes from ice age toward current warm conditions on the earth. We also performed Molecular Dynamics simulation at corresponding temperatures of all enzyme variants including 308, 318, and 328 K. It was found that mesophile enzyme has no distinct deviation of Root Mean Square Deviation (RMSD) and Radius of Gyration (Rg) values from equilibrium states at operating temperature of thermophile enzyme as well as its own optimum temperature. However, psychrophile enzyme undergoes more fluctuations with higher amplitude of change; particularly at 328 K. It was also found that initial increasing of RMSD and Rg for Psychrophile enzyme at all temperatures is occurred gradually; while, the increment of this structural parameters for thermophile enzyme at 328 K is occurred in a highly cooperative and switching manner demonstrating snap structural change of thermophile enzyme in its own temperature. By analysis of Root Mean Square Fluctuation values at different temperatures, we identified two flexible fragments in adenylate kinases so that different dynamic behavior of these regions in mesophile enzyme against operating temperatures of psychrophile and thermophile variants is critical in compensation of flexibility challenges at respective temperatures.